2007
DOI: 10.1161/01.res.0000261657.76299.ff
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of the NAD(P)H Oxidase Subunit p47 phox for Left Ventricular Remodeling/Dysfunction and Survival After Myocardial Infarction

Abstract: Accumulating evidence suggests a critical role of increased reactive oxygen species production for left ventricular (LV) remodeling and dysfunction after myocardial infarction (MI). An increased myocardial activity of the NAD(P)H oxidase, a major oxidant enzyme system, has been observed in human heart failure; however, the role of the NAD(P)H oxidase for LV remodeling and dysfunction after MI remains to be determined. MI was induced in wild-type (WT) mice (n=46) and mice lacking the cytosolic NAD(P)H oxidase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
152
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(171 citation statements)
references
References 66 publications
11
152
2
3
Order By: Relevance
“…In addition to gp91 phox , NADPH oxidase is composed of several other subunits including p22 phox , p40 phox , p47 phox , p67 phox and racl. Doerries et al have recently indicated that lack of p47 phox improved cardiac remodeling and ventricular function, indicating the importance of p47 phox in cardiac remodeling following MI (42). This observation suggests that the individual subunits of NADPH oxidase may differ in the effects they have on cardiac remodeling postMI.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to gp91 phox , NADPH oxidase is composed of several other subunits including p22 phox , p40 phox , p47 phox , p67 phox and racl. Doerries et al have recently indicated that lack of p47 phox improved cardiac remodeling and ventricular function, indicating the importance of p47 phox in cardiac remodeling following MI (42). This observation suggests that the individual subunits of NADPH oxidase may differ in the effects they have on cardiac remodeling postMI.…”
Section: Discussionmentioning
confidence: 98%
“…These differences in regulation, activation mechanism, subcellular location, and ROS generation translate into isoform-specific actions in isolated cellular models (9,19,22,33). In the heart, previous studies in mouse models of defective Nox2 activation or its deletion showed that Nox2 is detrimental during remodeling, causing increased hypertrophy, apoptosis, and contractile dysfunction (10)(11)(12)(13)(14)(15). The current results on Nox4, taken together with previous data on Nox2, indicate that the two isoforms contrast markedly in their effects on cardiac remodeling, with Nox2 being detrimental and Nox4 beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…In nonphagocytic cells, however, Nox2 and other Nox proteins generate low levels of ROS that are involved in intracellular signaling (9). Previous studies using Nox2-null mice and other models showed that Nox2 in the heart is involved in the development of cardiac hypertrophy and contractile dysfunction induced by angiotensin II, pressure overload, or myocardial infarction (10)(11)(12)(13)(14)(15). Nox4 differs from Nox2 and other Nox enzymes in that it is regulated mainly by its expression level and does not require agonist stimulation or association with regulatory subunits for activation (16)(17)(18).…”
mentioning
confidence: 99%
“…Theoretically, the lack of ROS production, notwithstanding increased nuclear NOX2 expression in ADAtreated cells, could be related to a lack of nuclear p47 phox expression, which is a crucial non-catalytic subunit, in induction of apoptosis, also in cardiomyocytes [25]. For this, we performed 3D confocal stackings to acquire optical sections of the cells to determine the exact intracellular location of p47 phox .…”
Section: Effect Of Ada and Hcy On Atp Levelsmentioning
confidence: 99%